Analisis Pengaruh Daya Tarik Promosi, Persepsi Harga dan Brand Image Terhadap Keputusan Pembelian Properti (Studi Kasus pada Perumahan Citra Raya City Jambi) - Laila Farhat; Marnas Marnas (Ekonomis: Journal of Economics and Business, 2022)
His study was conducted to analyze the effect of promotional attractiveness, price perception and brand image on property purchase decisions (Case Study on Citraraya City Jambi Housing). This study intends to analyze the effect of promotional attractiveness, price perception, and brand image on the purchase decision of Citra Raya City Jambi property. Based on the results of the study, it was obtained that the calculated F value was 13,290 > F table (2.58) at a significance level of 5%, thus it can be interpreted that promotional attractiveness, price perception, and brand image have an influence on property purchasing decisions. The coefficient objectivity test was carried out by means of F-count 13,290 > F-table (2.58) at a significance level of 5% and R-count = 0.736 > R(0.05)(18) = 0.243, meaning that the coefficient is significant. Thus the hypothesis H4 "Analysis of Promotional Attractiveness, Price Perception and Brand Image have an effect on Property Purchase Decisions". The value of r2 is 0.542, so the magnitude of the contribution of Promotional Attractiveness, Price Perception and Brand Image to Property Purchase Decisions is 54.2%, while the remaining 45.8% is influenced by other factors that are not included in the research variables.